Effect of heating parameters on sintering behaviors and properties of mullite whisker frameworks. (28th February 2018) - Zhang, Y M; Zeng, D J; Wang, B; Yang, J F
Abstract: Mullite whisker frameworks were fabricated by vapor–solid reaction with SiO2, Al2 O3 and AlF3 powders as the whisker forming agent at high temperatures. The effects of heating temperature and soaking time on the weight loss, liner shrinkage, porosity, microstructure and compressive strength were investigated. The results showed that with the increasing of the sintering temperature and soaking time, the weight loss and liner shrinkage of the samples increased and the porosities decreased due to the accelerated vapor–solid reaction, resulting in strong bonding and grain growth of the mullite frameworks. The compressive strength of the samples increased with increasing the sintering temperature from 1500 to 1650 °C, and decreased with the soaking time extended to more than 5 h for 1500 °C and 2 h for 1650 °C. A maximum compressive strength of 142 MPa at a porosity of 62.3% was obtained for the mullite whisker framework heated at 1500 °C for 5 h. The enhanced strength was attributed to the strong bonding strength and fine mullite grains resulting from a relative lower heating temperature and a modest soaking time.